Study Of Digital Marketing In India (Trinity Journal of Management, IT & Media (TJMITM), 2016)
Technology is now rapidly becoming crucial for the development of  India. Now, everything and everyone is getting digitalized, whether  it is private sector, public sector or even an individual. Most of the  organizations have understood the prospective of digital marketing  in India. They understood its time utility, cost effectiveness and  efficiency. Actually, Digital marketing is the marketing of goods and  services using various technologies to capture the new customers  and contain the existing one for various products. It is making the  task of marketing much easier for any organization. It is helping  them to understand their customers. They can now get immediate feedback about their products.  Now, the digitalization is giving an opportunity to the consumers  and producers to communicate with each other. This approach  of marketing is taking customer satisfaction to the next level.  Now, consumers themselves are making their own product for the  producers by giving their valuable suggestions continuously. The  research focus is to analyse the various aspects of digital marketing  and its impact on consumers, companies and the development of  the country.
Keywords: Digital marketing; customer; technology; India; product